Personal geographies - Taylor, Ellen Maureen (ELOPE (Ljubljana), 2016)
This paper examines the relationship between two 20th-century American poets, Elizabeth Coatsworth and her daughter, Kate Barnes. Both women mined their physical and personal geographies to create their work; both labored in the shadows of domineering literary husbands. Elizabeth's early poetry is economical in language, following literary conventions shaped by Eastern poets and Imagists of her era. Kate's work echoes her mother's painterly eye, yet is informed by the feminist poetry of her generation. Their dynamic relationship as mother and daughter, both struggling with service to the prevailing Western patriarchy, duties of domestication and docility, also inform their writing. This paper draws from Coatsworth's poems, essays, and memoir, and Barnes' poems, interviews, and epistolary archives, which shed light on her relationship with her renowned mother.
Keywords: American literature; ameriška književnost; ameriški pesniki; feminism; feminizem; imagizem; konfesionalna poezija; literarne študije; odnos mati-hči; patriarhalnost